R-STO photocatalyst as well as preparation method and application thereof
By preparing R-STO photocatalysts, the surface of SrTiO3 nanoparticles is loaded with RGO, rhodium, chromium and cobalt by using high-temperature molten salt method and photodeposition method, the problems of low photocatalytic water decomposition efficiency and poor material stability are solved, and the efficient decomposition of water and hydrogen to produce oxygen is achieved, which is suitable for large-scale applications.
Patent Information
- Application Number
- CN202510069266.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing photocatalytic water decomposition technology is low in efficiency, high carrier recombination rate, easy degradation of materials under operating conditions, difficult to achieve large-scale application, and poor selectivity for hydrogen production and many by-products.
Cubic phase SrTiO3 nanoparticles were prepared by high-temperature molten salt method, and RGO, rhodium, chromium and cobalt atoms were attached to the surface, and R-STO photocatalyst was deposited under simulated sunlight by photodeposition.
It improves the photogenerated carrier separation efficiency, enhances the oxygen production performance of photocatalytic decomposition of water, hydrogen analysis, and has good material stability, which is suitable for large-scale production.
Smart Images

Figure CN119793483A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic materials, and specifically relates to an R-STO photocatalyst and a preparation method and application thereof. Background Art
[0002] Photocatalytic complete water splitting is an innovative approach that aims to convert solar energy into hydrogen fuel by efficiently splitting water molecules into hydrogen and oxygen. The process typically involves semiconductor materials that can absorb sunlight and promote the necessary chemical reactions. However, photocatalytic water splitting still faces several key challenges: the overall efficiency of the photocatalytic process is generally low due to reasons including poor light absorption, carrier recombination, and insufficient reaction kinetics. Many photocatalysts degrade over time under operating conditions, reducing their effectiveness and lifetime. The transition from laboratory-scale systems to large-scale applications remains difficult because the process needs to be economically viable and efficient. Achieving high selectivity for hydrogen production compared to other reactions can be challenging, resulting in the production of unwanted byproducts. Addressing these issues requires continued research into new materials, innovative designs, and improved reaction conditions.
[0003] As an important perovskite semiconductor material, strontium titanate has significant application potential in the field of photocatalysis. It shows broad application prospects in the field of photocatalytic decomposition of water, hydrogen evolution and oxygen production. The strontium titanate prepared by the molten salt method of the present invention has a significant cubic phase crystal structure, which reduces the surface defects of the traditional preparation of strontium titanate and is conducive to the effective separation of photogenerated electron-hole pairs. RGO / SrTiO3 nanoparticles obtained by surface loading GO synchronous reduction, and R-STO photocatalysts are obtained by loading rhodium, chromium atoms and cobalt oxide on the surface of RGO / SrTiO3 nanoparticles using photodeposition technology. This scheme makes the material system have higher performance, and there are no related reports on the preparation scheme of R-STO photocatalyst for photocatalytic water decomposition. Summary of the invention
[0004] In order to solve the problems in the prior art, the present invention provides an R-STO photocatalyst and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] An R-STO photocatalyst, the preparation method of which comprises the following steps:
[0007] 1) grinding strontium chloride and SrTiO3 powders and transferring them to a muffle furnace for calcination, cooling naturally, washing three times with deionized water and drying to obtain cubic SrTiO3 nanoparticles;
[0008] 2) Add GO solution dropwise into deionized water, add SrTiO3 nanoparticles, stir evenly with magnetic force, then add ascorbic acid solution dropwise into the above solution and continue stirring for 0.5h; transfer the mixed solution into a hydrothermal kettle lined with polytetrafluoroethylene, place it in an oven for heating, cool naturally, wash and dry it, and obtain RGO / SrTiO3 nanoparticles;
[0009] 3) Dispersing RGO / SrTiO3 nanoparticles in a beaker containing 20 mL of deionized water, adding sodium hexachlororhodium solution, and using the photodeposition method to deposit rhodium ions on the catalyst surface under simulated sunlight;
[0010] 4) adding chromium nitrate nonahydrate solution to the mixed solution obtained in step 3), and using a photodeposition method to deposit chromium ions on the catalyst surface under simulated sunlight;
[0011] 5) adding a hexahydrate cobalt nitrate solution to the mixed solution obtained in step 4), and depositing cobalt ions on the catalyst surface under simulated sunlight using a photodeposition method;
[0012] 6) The mixed solution obtained in step 5) is filtered, washed and dried to obtain a final product named R-STO photocatalyst.
[0013] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 1), the strontium chloride is strontium chloride hexahydrate with a mass of 14.5 g, and the SrTiO3 powder is commercially available SrTiO3 with a mass of 1 g.
[0014] Furthermore, in the above-mentioned method for preparing the R-STO photocatalyst, in step 1), the calcination temperature is 1100° C. and the calcination time is 10 h.
[0015] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 2), the concentration of the GO solution is 1 mg / mL, the volume is 100 μL, and the mass of the SrTiO3 nanoparticles is 0.1 g.
[0016] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 2), the concentration of the ascorbic acid solution is 3.33 g / L, and the volume is 30 mL.
[0017] Furthermore, in the above-mentioned method for preparing a R-STO photocatalyst, in step 2), the heating temperature in the oven is 90° C. and the heating time is 6 hours.
[0018] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 3), the mass of the RGO / SrTiO3 nanoparticles is 20 mg, the concentration of the sodium hexachlororhodiumate solution is 0.59 mg / mL, and the volume is 126 μL.
[0019] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 4), the concentration of the chromium nitrate nonahydrate solution is 7.7 mg / mL and the volume is 6 μL.
[0020] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 5), the concentration of the cobalt nitrate hexahydrate solution is 2 mg / mL and the volume is 20 μL.
[0021] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 3), step 4) and step 5), the light source for simulating sunlight irradiation is a xenon lamp light source with a power of 148 mW and a light intensity.
[0022] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 3), the photodeposition time is 10 minutes.
[0023] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 4), the photodeposition time is 5 minutes.
[0024] Furthermore, in the above-mentioned method for preparing an R-STO photocatalyst, in step 5), the photodeposition time is 5 minutes.
[0025] Application of an R-STO photocatalyst as described in any one of the above in photocatalytic decomposition of water to produce hydrogen and oxygen.
[0026] Furthermore, the above application method is as follows: take the R-STO photocatalyst and evenly disperse it in 20mL of deionized water, continuously introduce argon gas into the reaction container at a rate of 40mL / min for 10min, seal the container, and perform photocatalytic decomposition of water to produce hydrogen and oxygen under a xenon lamp light source with a power of 300W to simulate sunlight irradiation conditions.
[0027] The beneficial effects of the present invention are:
[0028] 1. The present invention uses a high-temperature molten salt method, hydrothermal synthesis and photodeposition method to prepare the R-STO photocatalyst, which can effectively suppress the recombination efficiency of photogenerated electrons and holes, realize the efficient separation of photogenerated carriers, and has excellent photocatalytic water decomposition, hydrogen evolution and oxygen production performance under simulated sunlight.
[0029] 2. The preparation method of the present invention is simple, convenient, low-cost, mild in conditions, and is conducive to large-scale production.
[0030] 3. The R-STO photocatalyst prepared by the present invention has good photocatalytic cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 X-ray diffraction patterns of the SrTiO3 catalyst prepared in Example 1 and the R-STO-2 photocatalyst prepared in Example 3.
[0032] Figure 2 Fourier transform infrared spectra of the SrTiO3 catalyst prepared in Example 1, the R-STO-2 photocatalyst prepared in Example 3, and the RGO nanosheets prepared in Example 4.
[0033] Figure 3 Scanning electron microscope (SEM) images of the SrTiO3 catalyst prepared in Example 1, the R-STO-2 photocatalyst prepared in Example 3, and the RGO nanosheets prepared in Example 4.
[0034] Figure 4 The photoluminescence spectra of the SrTiO3 catalyst prepared in Example 1, the R-STO-2 photocatalyst prepared in Example 3, and the R-STO-1 and R-STO-3 photocatalysts prepared in Example 5 are shown.
[0035] Figure 5 The photocatalytic water decomposition activity diagram of the SrTiO3 catalyst prepared in Example 1, the R-STO-2 photocatalyst prepared in Example 3, and the R-STO-1 and R-STO-3 photocatalysts prepared in Example 5. DETAILED DESCRIPTION
[0036] Example 1
[0037] The preparation method of SrTiO3 nanoparticles is as follows:
[0038] 14.5 g of strontium chloride hexahydrate and 1 g of commercially available SrTiO3 powder were mixed and ground, and then transferred to a muffle furnace and calcined at 1100°C for 10 h. After natural cooling, the mixture was washed three times with deionized water and dried to obtain SrTiO3 nanoparticles.
[0039] Example 2
[0040] The preparation method of GO solution is as follows:
[0041] At 1°C, 1g of natural graphene was dispersed in 23mL of H2SO4. After continuous stirring for 50min, 6g of KMnO4 was added to the above solution at a very slow rate (about 25min). After continuous stirring for 3h, the mixed solution was transferred to 45°C and stirred for 45min to release heat by bubbling. Next, the mixed solution was placed in an environment of 80°C, and 60mL of distilled water was slowly (within 20min) added to the mixed solution. After stirring for 15min, 60mL of distilled water was added to the mixed solution to dilute it and pour in 5wt% hydrogen peroxide. The solution was washed several times by centrifugation with distilled water until the pH value of the supernatant after centrifugation was 6 to obtain a GO solution. After measuring the concentration of the obtained GO solution, 1mL of GO solution was taken and diluted to 1mg / mL
[0042] Example 3
[0043] The preparation method of R-STO catalyst is as follows:
[0044] 100 μL of the GO solution (concentration of 1 mg / mL) prepared in Example 2 was added dropwise to 30 mL of deionized water, and 0.1 g of the SrTiO3 nanoparticles prepared in Example 1 were added. After magnetic stirring, 30 mL of ascorbic acid solution (concentration of 3.33 g / L) was added dropwise to the above solution and continued to stir for 0.5 h. The mixed solution was transferred to a hydrothermal autoclave lined with polytetrafluoroethylene, placed in a 90 ° C oven and heated for 6 h. After natural cooling, it was washed three times and dried to obtain RGO / SrTiO3 nanoparticles.
[0045] 20mg of RGO / SrTiO3 nanoparticles were dispersed in a beaker containing 20mL of deionized water, and 126μL of sodium hexachlororhodium solution (concentration of 0.59mg / mL) was added, and photodeposited for 10min under a xenon lamp with a light intensity of 148mW; then 6μL of chromium nitrate solution (concentration of 7.7mg / mL) was added, and photodeposited for 5min; then 20μL of cobalt nitrate solution (concentration of 2mg / mL) was added, and photodeposited for 5min. Finally, the mixed solution was filtered, washed three times and dried to obtain the final target product named R-STO-2.
[0046] Example 4
[0047] 10 mL of the GO solution (concentration of 1 mg / mL) prepared in Example 2 was added dropwise to 50 mL of ascorbic acid solution (concentration of 200 g / L) and stirred for 0.5 h. The mixed solution was transferred to a hydrothermal reactor lined with polytetrafluoroethylene, placed in a 90°C oven and heated for 6 h. After natural cooling, it was washed three times and dried to obtain RGO nanosheets.
[0048] Example 5
[0049] The amount of GO solution in Example 3 was changed to 50 μL and 150 μL, respectively, and other operations remained unchanged. The final products were marked as R-STO-1 and R-STO-3, respectively.
[0050] Figure 1 X-ray diffraction patterns of the SrTiO3 catalyst prepared in Example 1 and the R-STO-2 photocatalyst prepared in Example 3. Figure 1 The characteristic peaks of SrTiO3 are located at 32.4°, 40.1°, 46.6°, 57.9°, 67.9°, and 77.5°, corresponding to the (110), (111), (200), (211), (220), and (310) crystal planes of cubic phase SrTiO3, respectively. This is completely consistent with the arrangement order of the standard card (PDF.84-0443) of cubic perovskite phase SrTiO3. No additional characteristic peaks were found in the XRD pattern of the R-STO-2 composite sample, which may be attributed to the fact that the RGO content in the composite sample is less than 1% and cannot be detected. However, in the Fourier transform infrared spectrum ( Figure 2 ) shows that the absorption peak of the R-STO-2 composite sample corresponds to the RGO nanosheet prepared in Example 4, indicating that the R-STO photocatalyst was successfully prepared. Scanning electron microscope (SEM) image ( Figure 3 ) shows that the morphology of SrTiO3 nanoparticles is mainly regular hexahedron, and the hexahedral structure of SrTiO3 can still be clearly seen in the SEM image of the R-STO-2 composite sample. However, through careful observation, it is found that the surface of the sample seems to be evenly covered with a layer of RGO. In the photoluminescence spectrum ( Figure 4 ) It can be seen that the emission peaks of all composite samples are lower than the emission peak of SrTiO3, indicating that there is good charge transfer at the interface between SrTiO3 and RGO.
[0051] Example 6
[0052] Application of photocatalysts in catalytic decomposition of water under light:
[0053] Under normal temperature and pressure conditions, 20 mg of the catalyst was placed in a reactor containing 20 mL of distilled water, and argon was introduced into the reactor at a rate of 40 mL / min for 10 min to exhaust the air; under the condition of 300 W xenon lamp light source simulating sunlight irradiation, 1000 μL of gas in the reactor was extracted at 10 min, 20 min, 30 min, 60 min, 90 min, and 120 min, respectively, and the collected catalytic products were quantitatively analyzed by gas chromatograph.
[0054] Figure 5The photocatalytic water decomposition activity diagram of the SrTiO3 catalyst prepared in Example 1, the R-STO-2 photocatalyst prepared in Example 3, and the R-STO-1 and R-STO-3 photocatalysts prepared in Example 5, the peak area of the extracted gas was measured by gas chromatograph, and then converted into the amount of its substance by calculation, such as Figure 5 As shown, after 1 hour, the H2 yield of the SrTiO3 catalyst was 15.9 mmol / g, and the O2 yield was 7.4 mmol / g; the H2 and O2 yields of the composite samples R-STO-1, R-STO-2 and R-STO-3 photocatalysts were 35.8 mmol / g and 16.2 mmol / g, 43.0 mmol / g and 19.4 mmol / g, and 25.1 mmol / g and 9.9 mmol / g, respectively. The yield of R-STO-2 reached 2.7 times that of the original sample, and the hydrogen evolution and oxygen production rates were higher than those of other related catalysts currently studied.
Claims
1. An R-STO photocatalyst, characterized in that: The preparation method comprises the following steps: 1) grinding strontium chloride and SrTiO3 powders and transferring them to a muffle furnace for calcination, cooling naturally, washing three times with deionized water and drying to obtain cubic SrTiO3 nanoparticles; 2) Add GO solution dropwise into deionized water, add SrTiO3 nanoparticles, stir evenly with magnetic force, then add ascorbic acid solution dropwise into the above solution and continue stirring for 0.5h; transfer the mixed solution into a hydrothermal kettle lined with polytetrafluoroethylene, place it in an oven for heating, cool naturally, wash and dry it, and obtain RGO / SrTiO3 nanoparticles; 3) Dispersing RGO / SrTiO3 nanoparticles in a beaker containing 20 mL of deionized water, adding sodium hexachlororhodium solution, and using the photodeposition method to deposit rhodium ions on the catalyst surface under simulated sunlight; 4) adding chromium nitrate nonahydrate solution to the mixed solution obtained in step 3), and using a photodeposition method to deposit chromium ions on the catalyst surface under simulated sunlight; 5) adding a hexahydrate cobalt nitrate solution to the mixed solution obtained in step 4), and depositing cobalt ions on the catalyst surface under simulated sunlight using a photodeposition method; 6) The mixed solution obtained in step 5) is filtered, washed and dried to obtain a final product named R-STO photocatalyst.
2. The R-STO photocatalyst according to claim 1, characterized in that: In step 1), the strontium chloride is strontium chloride hexahydrate with a mass of 14.5 g, and the SrTiO3 powder is commercially available SrTiO3 with a mass of 1 g; in step 2), the concentration of the GO solution is 1 mg / mL, the volume is 100 μL, the mass of the SrTiO3 nanoparticles is 0.1 g, the concentration of the ascorbic acid solution is 3.33 g / L, and the volume is 30 mL.
3. The R-STO photocatalyst according to claim 1, characterized in that: In step 1), the calcination temperature is 1100° C. and the calcination time is 10 h.
4. The R-STO photocatalyst according to claim 1, characterized in that: In step 2), the heating temperature in the oven is 90° C. and the heating time is 6 hours.
5. The R-STO photocatalyst according to claim 1, characterized in that: In step 3), the mass of the RGO / SrTiO3 nanoparticles is 20 mg, the concentration of the sodium hexachlororhodiumate solution is 0.59 mg / mL, and the volume is 126 μL.
6. The R-STO photocatalyst according to claim 1, characterized in that: In step 4), the concentration of the chromium nitrate nonahydrate solution is 7.7 mg / mL and the volume is 6 μL.
7. The R-STO photocatalyst according to claim 1, characterized in that: In step 5), the concentration of the cobalt nitrate hexahydrate solution is 2 mg / mL and the volume is 20 μL.
8. The R-STO photocatalyst according to claim 1, characterized in that: In step 3), step 4) and step 5), the light source for simulating sunlight irradiation is a xenon lamp light source with a power of 148 mW; in step 3), the light deposition time is 10 min; in step 4) and step 5), the light deposition time is both 5 min.
9. Use of an R-STO photocatalyst as claimed in any one of claims 1 to 8 in photocatalytic decomposition of water to generate hydrogen and oxygen.
10. The use according to claim 9, characterized in that: The method is as follows: take the R-STO photocatalyst and evenly disperse it in 20mL of deionized water, continuously introduce argon gas into the reaction container at a rate of 40mL / min for 10 minutes, seal the container, and carry out photocatalytic decomposition of water to produce hydrogen and oxygen under the conditions of 300W xenon lamp light source simulating sunlight irradiation.
Citation Information
Patent Citations
Graphene / titanate nanometer composite visible-light activated photocatalyst and preparation method thereof
CN102847529A
Construction method and application of Z-type photocatalytic water splitting reaction system based on GaN: ZnO solid solution
CN115121278A
Preparation method and application of g-C3N4 / MnWO4 heterojunction photocatalyst
CN117899915A
PT / SRTiO3 PHOTOCATALYST FOR PRODUCTION OF CYCLOALKANOLS AND CYCLOALKANONES FROM CYCLOALKANES
US20190276383A1
Semiconductor particles used in water-splitting photocatalyst, photocatalyst formed of semiconductor particles, and synthesis method thereof
US20230096060A1